Pengaruh Pengalaman Kerja, Independensi, Objektivitas, dan Motivasi terhadap Kualitas Hasil Pemeriksaan Auditor Inspektorat Provinsi Kalimantan Tengah - Boby Segah (Anterior Jurnal, 2018)
The audit organization in Indonesia is divided into two, namely the Government External auditor conducted by the Supreme Audit Agency (BPK) and the Government Internal Auditor or better known as the Internal Controller of the Government (APIP). The function of the internal auditor is to carry out an internal audit function which is an independent appraisal function within an organization to test and evaluate the organization's activities undertaken. In addition, internal auditors are also expected to contribute more to improving efficiency and effectiveness in order to improve organizational performance. One of the units conducting an audit/examination of the Regional Government is the Regional Inspectorate. The Inspectorate Auditor of Central Kalimantan Province only conducts an examination in the form of a review of the Local Government Financial Statements to provide limited confidence in the quality of the Regional Financial Report not the opinion or opinion on the Financial Statement, but only the recommendation. This is stated in the Minister of Home Affairs Regulation No. 4 of 2008. The Auditor at the Inspectorate of Central Kalimantan Province is a government internal auditor with the same examination object each examination period, it will appear familiarity between the auditor with the object of examination. The emerging familiarity can lead to the independence of the auditor being disrupted so that the quality of the examination results decreases. The Inspectorate Auditor of Central Kalimantan Province conducts an examination based on the belief that he will gain personal pleasure, such as the enjoyment of improving intellectual ability.